2017
DOI: 10.1042/bcj20170152
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding architecture of the multi-modular α-1,6-glucosyltransferase from Paenibacillus sp. 598K, which produces α-1,6-glucosyl-α-glucosaccharides from starch

Abstract: sp. 598K α-1,6-glucosyltransferase (Ps6TG31A), a member of glycoside hydrolase family 31, catalyzes exo-α-glucohydrolysis and transglucosylation and produces α-1,6-glucosyl-α-glucosaccharides from α-glucan via its disproportionation activity. The crystal structure of Ps6TG31A was determined by an anomalous dispersion method using a terbium derivative. The monomeric Ps6TG31A consisted of one catalytic (β/α)-barrel domain and six small domains, one on the N-terminal and five on the C-terminal side. The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The crystal structure of GH31 6‐α‐glucosyltransferase from Paenibacillus sp. 598K (Ps6TG31A) has also been reported . Ps6TG31A shows transglucosylation activity against isomaltooligosaccharides and shares some resemblance to FjDex31A, as both enzymes catalyze transglucosylation to form the α‐1,6‐linkage.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The crystal structure of GH31 6‐α‐glucosyltransferase from Paenibacillus sp. 598K (Ps6TG31A) has also been reported . Ps6TG31A shows transglucosylation activity against isomaltooligosaccharides and shares some resemblance to FjDex31A, as both enzymes catalyze transglucosylation to form the α‐1,6‐linkage.…”
Section: Resultsmentioning
confidence: 98%
“…Structural analysis of Ps6TG31A in complex with isomaltohexaose as well as acarbose, an inhibitor of α‐glucosidases, has revealed that Ps6TG31A has multiple substrate‐binding sites . Acarbose binds to subsites −1, +1, +2, and +3 while the β‐isomaltotetraose unit binds to subsites +1a, +2a, +3a, and +4a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The N-terminal catalytic domain consists of a five-bladed b-propeller (Gln21-Gly325), as in other GH clan-F enzymes, and the C-terminal domain (PcCBM35) takes a β-jellyroll fold (Thr326-Tyr448) structure, as in previously reported CBM35s (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Overall Structure Of Pc13gal43amentioning
confidence: 80%
“…Although there was very little similarity between the sequence of this module and that of other characterized proteins, proteins structurally similar to this structure were found in the PDB using the DALI server including a number of carbohydrate‐binding module family 35 (CBM35) , including CBM35 of Paenibacillus sp. 598K α‐1,6‐glucosyltransferase (PsCBM35‐1; RMSD = 1.9 Å for the 112 Cα atoms, a.a. sequence identity = 18.8%; PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5X7O) , CBM35 of B. circulans T‐3040 cycloisomaltooligosaccharide glucanotransferase (BcCBM35‐1; RMSD = 2.1 Å for the 117 Cα atoms, a.a. sequence identity = 21.4%; PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3WNO) , and CBM35 of Clostridium thermocellum (CtCBM35; RMSD = 1.9 Å for the 113 Cα atoms, a.a. sequence identity = 18.6%; PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=2WZ8) . CBM35s are accompanied by catalytic domains, including those for xylanase, glucanase, glucosaminidase, mannanase, and galactanase activities, and function to bind their substrate saccharides to assist the catalytic domains.…”
Section: Resultsmentioning
confidence: 99%